CHANGES IN SKIN MICROCIRCULATION ON THE ANTERIOR ABDOMINAL WALL OF PATIENTS WITH ACUTE SURGICAL PATHOLOGY - Кристина Валерьевна Валиахмедова; Андрей Михайлович Алексеев; Андрей Игоревич Баранов; Сергей Викторович Кемеров; Наталья Павловна Блинова (Медицина в Кузбассе)
Objective. Assessment of perfusion changes in a tissue of the wound area in patients with acute surgical pathology.